Населення Лівобережної України давньоруської доби за матеріалами антропології - Рудич, Т.О. (Археологія, 2009)
Статтю присвячено антропологічним дослідженням населення давньоруського часу лісостепової частини Дніпровського Лівобережжя. Статья посвящена антропологическим исследованиям состава населения древнерусского времени лесостепной части Днепровского Левобережья. Результаты анализа дают автору возможность говорить о принадлежности большей части населения региона к долихокранному с среднешироким лицом морфотипу, характеризующему также довольно значительный массив населении с территории расселения дреговичей, радимичей, смоленских кривичей и в котором ощущается наличие балтского субстрата. Генетические связи с популяциями Правобережья демонстрирует некоторая часть населения Переяславской (г. Переяслав и его округа) и Черниговской земель (среднее Подесенье). В отдельных группах фиксируется влияние кочевого населения и эпизодически присутствие норманов. The article is devoted to the anthropological research on composition of the population in the Ancient Rus period on the forest-steppe territory of the left bank of the Dnipro River region. The results of the analysis allow the author to conclude that most of the habitants of this region belonged to the dolichocephalic with a middle-wide face morphological type, which is also peculiar to the great part of the habitants of the territories settled by Dregovychi, Radymychi, Kryvychi of Smolensk and in which the Baltic substrate is noted. Genetic links with the populations of the right bank of the Dnipro River region are evidenced on a certain part of the population of Pereyaslav (Pereyaslav city and its suburbs) and Chernihiv (the Desna River middle region) lands. In some groups the influence of the nomads and rarely the Normans is identified.